Context-dependent interpretation of the prognostic value of BRAF and KRAS mutations in colorectal cancer - Popovici, Vlad; Budinska, Eva; Bosman, Fred T; Tejpar, Sabine; Roth, Arnaud D; Delorenzi, Mauro (BMC cancer, 2013)
BACKGROUND: The mutation status of the BRAF and KRAS genes has been proposed as prognostic biomarker in colorectal cancer. Of them, only the BRAF V600E mutation has been validated independently as prognostic for overall survival and survival after relapse, while the prognostic value of KRAS mutation is still unclear. We investigated the prognostic value of BRAF and KRAS mutations in various contexts defined by stratifications of the patient population. METHODS: We retrospectively analyzed a cohort of patients with stage II and III colorectal cancer from the PETACC-3 clinical trial (N = 1,423), by assessing the prognostic value of the BRAF and KRAS mutations in subpopulations defined by all possible combinations of the following clinico-pathological variables: T stage, N stage, tumor site, tumor grade and microsatellite instability status. In each such subpopulation, the prognostic value was assessed by log rank test for three endpoints: overall survival, relapse-free survival, and survival after relapse. The significance level was set to 0.01 for Bonferroni-adjusted p-values, and a second threshold for a trend towards statistical significance was set at 0.05 for unadjusted p-values. The significance of the interactions was tested by Wald test, with significance level of 0.05. RESULTS: In stage II-III colorectal cancer, BRAF mutation was confirmed a marker of poor survival only in subpopulations involving microsatellite stable and left-sided tumors, with higher effects than in the whole population. There was no evidence for prognostic value in microsatellite instable or right-sided tumor groups. We found that BRAF was also prognostic for relapse-free survival in some subpopulations. We found no evidence that KRAS mutations had prognostic value, although a trend was observed in some stratifications. We also show evidence of heterogeneity in survival of patients with BRAF V600E mutation. CONCLUSIONS: The BRAF mutation represents an additional risk factor only in some subpopulations of colorectal cancers, in others having limited prognostic value. However, in the subpopulations where it is prognostic, it represents a marker of much higher risk than previously considered. KRAS mutation status does not seem to represent a strong prognostic variable.
Keywords: Recurrence; protoonkogenní proteiny p21(ras); kolorektální nádory; mutace; retrospektivní studie; Neoplasm Grading; prognóza; Neoplasm Staging; Proto-Oncogene Proteins; Ras proteiny; recidiva; Proto-Oncogene Proteins B-raf; lidé; Humans; stupeň nádoru; Colorectal Neoplasms; Prognosis; Proto-Oncogene Proteins p21(ras); Mutation; Retrospective Studies; ras Proteins; protoonkogenní proteiny B-Raf; staging nádorů; protoonkogenní proteiny